Does Independent Commissioner Decrease The Positive Association Between Transfer Pricing And Tax Avoidance? - Deviansyah, M. Rafli; Nugroho, Edi; Firmansyah, Amrie (Educoretax, 2024)
Indonesia's tax ratio has not increased proportionally to projected tax revenues. A low tax ratio indicates tax avoidance. One type of tax avoidance strategy is transfer pricing. The presence of independent commissioners is expected to suppress transfer pricing practices as a forum for tax avoidance by management. This research examines the contribution of transfer pricing to tax avoidance practices. The study also investigates the moderation role of independent commissioners on managers' tax avoidance actions. The sample selection was carried out purposely on multinational manufacturing companies listed from 2019 to 2022 on the Indonesia Stock Exchange, resulting in 12 multinational manufacturing companies as samples. This research utilizes quantitative methods through panel data regression analysis. The test result finds that transfer pricing positively influences tax avoidance. However, the independent commissioner succeeds in weakening the positive influence of transfer pricing on tax avoidance. This indicates that independent commissioners have difficulty influencing management or operational-related decisions. This research implies that the Directorate General should focus on companies with high related party transactions to indicate that the company is likely to commit tax avoidance. This focus on supervision is considered to be able to increase Indonesia's tax revenue and ratio.